Erinnerungskultur im Deutschunterricht – Reflexionen, Erfahrungen und Empfehlungen aus Karaganda - Buck, K. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
My contribution discusses the question of whether the study of cultures of remembrance can be implemented in language teaching, especially German language teaching, what the benefits of such attempts are, and how they can be most fruitfully undertaken. To clarify the key term, the concept of ‘culture of remembrance’ signifies a ‘collective term for all non-scientific uses of history in the public sphere’ (1; 16). As this necessarily includes a multitude of rich and varied material that can be brought to use in language teaching, I argue that the discussion of cultures of remembrance is particularly suitable in order to make language lessons more attractive. Furthermore, I suggest that dealing with cultures of remembrance offers three specific positive learning outcomes that all combine the acquisition of ‘knowledge’ and ‘transferable skills’.
Неміс тілі сабағындағы есте сақтау мəдениеті: ойлар мен ұсыныстар (Е.А.Бөкетов атындағы ҚарМУ жұмысы тəжірибесінен)
Культура памяти на занятиях немецкого языка: размышления и рекомендации (из опыта работы в КарГУ им. Е.А.Букетова)
Keywords: culture of remembrance; language teaching; German; German language teaching; history; transferable skills